Whole exome sequencing in the Framingham Heart Study identifies rare variation in HYAL2 that influences platelet aggregation - Eicher, John D.; Chen, Ming-Huei; Pitsillides, Achilleas N.; Lin, Honghuang; Veeraraghavan, Narayanan; Brody, Jennifer A.; Metcalf, Ginger A.; Muzny, Donna M.; Gibbs, Richard A.; Becker, Diane M.; Becker, Lewis C.; Faraday, Nauder; Mathias, Rasika A.; Yanek, Lisa R.; Boerwinkle, Eric; Adrienne Cupples, L.; Johnson, Andrew D. (Thrombosis and Haemostasis, 2017)
Inhibition of platelet reactivity is a common therapeutic strategy in secondary prevention of cardiovascular disease. Genetic and environmental factors influence inter-individual variation in platelet reactivity. Identifying genes that contribute to platelet reactivity can reveal new biological mechanisms and possible therapeutic targets. Here, we examined rare coding variation to identify genes associated with platelet reactivity in a population-based cohort. To do so, we performed whole exome sequencing in the Framingham Heart Study and conducted single variant and gene-based association tests against platelet reactivity to collagen, adenosine diphosphate (ADP), and epinephrine agonists in up to 1,211 individuals. Single variant tests revealed no significant associations (p<1.44×10–7), though we observed a suggestive association with previously implicated MRVI1 (rs11042902, p = 1.95×10–7). Using gene-based association tests of rare and low-frequency variants, we found significant associations of HYAL2 with increased ADP-induced aggregation (p = 1.07×10–7) and GSTZ1 with increased epinephrine-induced aggregation (p = 1.62×10–6). HYAL2 also showed suggestive associations with epinephrine-induced aggregation (p = 2.64×10–5). The rare variants in the HYAL2 gene-based association included a missense variant (N357S) at a known N-glycosylation site and a nonsense variant (Q406*) that removes a glycophosphatidylinositol (GPI) anchor from the resulting protein. These variants suggest that improper membrane trafficking of HYAL2 influences platelet reactivity. We also observed suggestive associations of AR (p = 7.39×10–6) and MAPRE1 (p = 7.26×10–6) with ADP-induced reactivity. Our study demonstrates that gene-based tests and other grouping strategies of rare variants are powerful approaches to detect associations in population-based analyses of complex traits not detected by single variant tests and possible new genetic influences on platelet reactivity.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Epidemiological studies; platelet physiology; polymorphisms; thrombosis; gene mutations